Chapter Il «sistema dell'egoismo universale» e la condizione presente dell'Italia - Polizzi, Gaspare (Studi e saggi, 2020)
I intend to deal with the political thought of Giacomo Leopardi, especially in the Zibaldone, according to his conceptions on the contrast between reason and nature and on the contrast between ancient and modern, focusing attention on his analysis of the morale of the Italians, in order to identify their original line of interpretation in the analysis of the relationship between individuals and nations in the modern age, and in Italy in particular. The analysis of his political reflection cannot be separated from that of his moral and anthropological vision on the human condition. I dwell on three moments of his moral, social and anthropological vision of the nation, with a focus on the theme of individualism and the system of universal selfishness typical of Modernity.